Perancangan Aplikasi Manajemen Pengiriman Barang Berbasis Dekstop Di PT. Mitra Dua Sehati - Aditya Bayu Eko Sagoro; Agus Baskoro Hidayat; Amandus Durung; Thoyyibah Tanjung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This research was conducted at PT. MITRA DUA SEHATI, South Tangerang branch, which is located at Jl. Pahlawan Seribu Ruko BSD Sektor 7 Blok RO. No 73, South Tangerang City, Banten. The author conducted this research to produce an application in the form of a desktop-based freight management system aimed at PT. MITRA DUA SEHATI. The data collection technique used is through interviews or interviews, namely by contacting the resource person directly, in this case the author directly meets company employees who are related to this research, and by observation, namely direct observation of the object of the problem in the field. From the results of interviews and observations, the authors began to find solutions to the problems contained in the system used today. This delivery management system is made using the waterfall development model. Starting from analysis, design, implementation, testing, to maintenance. With this application, it is expected that the service performance of PT. MITRA DUA SEHATI especially in the export department.